Self Regelated Through Mathematics in Contexts (Mic) Approach Based on Local Culture Module to Improve Math Representation - Ardhana Kisno Saputra, Rifky; Sukestiyarno, Sukestiyarno; Karomah Dwidayati, Nur (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study is to describe the mathematical representation ability of students based on self regulated and module-based learning with a Mathematics In Contexts (MIC) approach with local culture. This research is a mixed method type of concurrent embedded design, with the subject of the research being the VIII MTs grade students. Negeri 1 Lamongan. The results obtained are Mentoring with a module-based MIC approach containing local culture effective towards mathematical representation with an average completeness above 70 with a value of 77.96; there is a positive influence of self regulated on the ability of representation of 73.1%; The mathematical representation ability of students has increased by 0.48 with the medium category. The ability of student representation can be classified into three aspects including visual aspects, symbolic aspects and verbal aspects. Students with high self regulated are able to master the three aspects of representation very well indicated by the average value obtained in the visual aspect of 100 then in the symbolic aspect 91.07 and in the verbal aspect 79.17. Students with self regulated are mastering visual and verbal aspects that stand out by getting an average rating of 87.50 in the visual aspect and 79.17 in the verbal aspect, while in the symbolic aspect getting an average score of 66.07. Students with low self regulated are able to master the verbal and visual aspects well, namely by obtaining a verbal average value of 70.83 and a mean visual value of 67.50 while the symbolic aspect obtains an average score of 51.79. Based on the results of the study, it is suggested in doing assistance with students who have moderate and low self regulated more intensively so that students are more independent, enthusiastic, and recognize their own potential for their mathematical representation abilities.